Development, expression and characterization of humanized anti-c2 monoclonal antibody / Suba Dharshanan A/L Panja Bernam - Suba Dharshanan, Panja Bernam (2012)

(untitled)
Humanized monoclonal antibodies (mAbs) are widely used for diagnosis and treatment of cancer due to their reduced immunogenicity and high specificity. In this project, we aimed to develop procedures to produce, with high efficiency in terms continuity of production, lowered cost and increased speed, humanized mAbs against C2-antigen (hum-C2 mAbs), a marker specifically expressed in colorectal and ovarian cancer, from mAb of mouse origin. The resulting hum-C2 mAbs must still retain their original specificity and functionality, but possess reduced immunogenicity. Two methods of humanization were compared to identify potential immunogenic mouse amino acids in the variable regions: a deimmunization method and a logical approach method using IgBLAST software. The respective amino acids were then replaced with their corresponding human residues by overlapping-PCR mutagenesis. The hum-C2 mAbs were expressed in NS0 mammalian cells. To decrease the time to identify and isolate high-producing transfectomas secreting hum-C2 mAbs, ClonePix FL which is a highthroughput, rapid and automated system, was employed to screen large numbers of transfectomas in a short period of time with increased probability of obtaining rare and precious high-producing cells. The high-producing NS0 transfectomas were adapted to serum-free media because the use of serum involves many ethical, safety and scientific complications. An automated liquid chromatography system, Äktaprime Plus, was used to purify hum-C2 mAb instead of the conventional method of antibody purification which is time-consuming, laborious and prone to errors. In terms of functionality, the hum-C2 mAbs produced by both humanization methods were still able to bind iv specifically to C2-antigen expressed on the surface of colorectal cancer cells (SW1116) in vitro. However, in terms of immunogenicity, only the humanized antibodies developed by deimmunization method had lower immunogenicity in Macaca fascicularis compared to chimeric and mouse anti-C2 mAbs. This clearly indicated the superiority of deimmunization method and demonstrated the fact that it could not be substituted by the logical approach method. Unfortunately, the use of overlapping-PCR mutagenesis to humanize mouse residues in the deimmunization method frequently results in undesired mutations which cause the method to be time-consuming and thus is not cost-effective. Thus, we substituted the conventional protocol with a method using synthetic DNA coding for the hum-C2 variable regions which were then transfected into NS0 and CHO mammalian cells using both pFUSE and UCOE expression systems. However we found that pFUSE vectors only worked for NS0 cells and UCOE vectors only for CHO cells. It was also found that the level of expression of hum-C2 mAbs in CHO cells using UCOE vectors was 100 times higher than NS0 cells transfected with pFUSE vectors. In addition, the use of UCOE vectors in CHO cells produced a greater number of high-producing and stable transfectomas. Hence, it was concluded that the best approach to produce hum-C2 mAbs is by using synthetic DNA coding the variable regions cloned into UCOE expression vectors and transfected in CHO cells. The use of ClonePix FL and Äktaprime Plus systems also allows the isolation of high-producing transfectomas and purification of humanized mAbs to be performed efficiently and quickly.